Mathematical and Computer Simulation of the Interconnected Processes Mass, Heat and Moisture Transfer in Horizontal Soil Media (Моделювання, керування та інформаційні технології, 2019)
The nonlinear mathematical model of a interconnected processes of moisture transfer, mass and heat transfer in horizontal soil layer is presented. The  numerical solution of the respective boundary value problem was obtained by the method of finite differences using the monotonic scheme. Software was created on the basic of developed algorithms and a series of numerical experiments were done.